2020
DOI: 10.3389/fimmu.2020.551441
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Nitric Oxide, Oxidative Stress, Eryptosis, Red Blood Cell Microparticles, and Vascular Function in Sickle Cell Anemia

Abstract: Chronic hemolysis, enhanced oxidative stress, and decreased nitric oxide (NO) bioavailability promote vasculopathy in sickle cell anemia (SCA). Oxidative stress and NO are known to modulate eryptosis in healthy red blood cells (RBCs); however, their role in SCA eryptosis and their impact on the genesis of RBC-derived microparticles (RBC-MPs) remains poorly described. RBC-MPs could play a role in vascular dysfunction in SCA. The aims of this study were to evaluate the roles of oxidative stress and NO in eryptos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 69 publications
1
51
1
Order By: Relevance
“…In this setting, accumulation of oxidative damage results in decreased deformability and generation of RBC-MPs. A recent study also demonstrated the key role of oxidative stress in RBC deformability and the release of RBC-MPs in the context of sickle cell anemia [ 26 ]. The application of omics technologies, including metabolomics, lipidomics, and proteomics, has contributed significantly to the understanding of RBC responses to oxidative stress [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this setting, accumulation of oxidative damage results in decreased deformability and generation of RBC-MPs. A recent study also demonstrated the key role of oxidative stress in RBC deformability and the release of RBC-MPs in the context of sickle cell anemia [ 26 ]. The application of omics technologies, including metabolomics, lipidomics, and proteomics, has contributed significantly to the understanding of RBC responses to oxidative stress [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Vascular damage in ACS is at least partially mediated by generation of oxygen-related molecules, such as superoxide (O 2 − ), hydrogen peroxide (H 2 O 2 ), peroxynitrite (ONOO − ), and the hydroxyl (•OH) radical [ 5 ]. Enhanced intravascular hemolysis can lead to an accumulation of hemoglobin (Hb) and heme in plasma, which in turn decreases bioavailability of nitric oxide (NO) and enhances ROS generation [ 2 ]. Moreover, the continuous oxidation of the heme iron in Hb (auto-oxidation) and impaired anti-oxidant capacity promote a pro-oxidative environment in sickle erythrocytes, which compromises overall redox balance in these cells and affects their metabolic state.…”
Section: H 2 O 2 : a Pneumocmentioning
confidence: 99%
“…Sickle cell disease (SCD) arises from homozygous single nucleotide polymorphisms (SNP) in the sixth codon of the β-globin gene (HbSS) on chromosome 11 which causes substitution of a single valine (Val) residue for glutamic acid (Glu) [ 1 ]. As a consequence, HbSS can polymerize under deoxygenation and mediates the sickling of erythrocytes [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several findings favor the primary involvement of oxidative stress in vesiculation ( Szigyarto et al, 2018 ; Nader et al, 2020 ): (I) MVs are enriched in antioxidant enzymes and irreversibly oxidized Hb ( Sudnitsyna et al, 2020 ); (II) some studies have indicated that treatment with oxidants decreased vesiculation, whereas antioxidants have an opposite effect ( Stowell et al, 2013 ; Nader et al, 2020 ). Oxidative stress, through the effects of ROS, may trigger both mechanisms of vesiculation—the clustering of Band-3 and the accumulation of intracellular Ca 2+ .…”
Section: Oxidative Stress and Membrane Sheddingmentioning
confidence: 99%